Mathematics
h8ingreality
2015-11-16 01:48:57
Determine whether the two expressions are equivalent. Explain your reasoning. 8. (n²+ 4) - n² and 4n 9. 3x + 5 and 2(x + 3) 10. 15 - 6x and 15(1 - 6x) 11. (y + y + 2 + y) + 3y and 6y + 2 12. 8y- 3 + 10y and 3(6 - 1)
ANSWERS
Emmuh
2015-11-16 06:42:03

Let us evaluate each pair of expressions one at a time. 8. (n²+4) - n² and 4n.     (n²+4) - n² = n²+ 4 - n² = 4 which is not equal to 4n.     NOT EQUIVALENT 9. 3x + 5 and  2(x + 3)     2(x + 3) = 2x + 6  which is not equal to 3x + 5.     NOT EQUIVALENT 10. 15 - 6x and  15(1 - 6x)     15(1 - 6x) = 15 - 90x which is not equal to 15 - 6x     NOT EQUVALENT 11. (y + y + 2 + y) + 3y and 6y + 2     (y +y +2 + y) + 3y = y+y+y +2 + 3y = 3y + 2 + 3y = 6y + 2.     It matches the other expression.     EQUIVALENT 12. 8y - 3 + 10y and 3(6 - 1)     8y - 3 + 10y = 8y + 10y - 3 = 18y - 3     3(6 - 1) = 3(5) = 15     The two expressions do not match.     NOT EQUIVALENT. Answer: Only the expressions in number 11 are equivalent.

ADD ANSWER